High resolution LC–ESI-TOF-mass spectrometry method for fast separation, identification, and quantification of 12 isoflavones in soybeans and soybean products. (1st June 2015) - Lee, Mi Jin; Chung, Ill-Min; Kim, Hunjung; Jung, Mun Yhung
Highlights: A LC–ESI-TOF-MS was successfully established for the quantification of isoflavones. The established method has low LOD, wide range of linearity, and high precision and repeatability. Twelve isoflavones in soybeans fully separated, identified and quantified within 12 min separation time. Abstract: A high resolution LC–ESI-TOF-MS analytical method was established for the rapid isolation, identification, and quantification of 12 isoflavones in soybean and soybean products. Individual isoflavones were identified on the basis of the accurate mass data of their respective protonated mass ions, Na or K adduct ions, fragment ions, and isotope ion patterns. The protonated mass ions of isoflavones were extracted for their quantification in soybean products. Twelve different isoflavones in the soybean products were fully separated, identified and quantified within 12 min separation time. The established LC–TOF/MS was an effective analytical method for the simultaneous characterization and quantification of isoflavones with exceptionally short analytical time, high selectivity, a high linearity ( r 2  > 0.992) in a wide range, low LOD and LOQ, high precision, inter-and intra-day repeatability, and no significant matrix effect. Furthermore, it requires simple sample preparation procedure (solvent extraction, dilution, and syringe filtration).